Speech Disorder in Anterior Open Bite (AOB): Systematic Review: Speech Disorder pada Anterior Open Bite (AOB): Systematic Review - Sari, Nendika Dyah Ayu Murika; Utomo, Rinaldi Budi (Dentika: Dental Journal, 2022)
There have been numerous researches showing that articulation disorders and malocclusion are linked. The most prevalent malocclusion in speech or articulation disorders is anterior open bite (AOB). Excessive propulsion of the tongue forward when articulating phonemes causes altered articulation in patients with open bites, as the tongue is in a more forward posture. The presence of this speech disorder can have a negative impact on a person's quality of life, although there hasn't been much research done on the impacts of AOB in cases of speech disorders in children. This study was to look at the link between speech disorders and the occurrence of anterior open bites (AOB) in a comprehensive way. Search results of research on four databases, namely ScienDirect, PubMed, Spingerlink, and Google Scholar, are displayed. The keywords used include speech disorder, articulation disorder, open bite, anterior open bite.Â  Five articles were selected using case control and cross-sectional methods in their research. The sample with AOB in this study was analyzed to determine the presence of speech disorders. The five articles gave similar results, showing that patients with malocclusion, especially AOB, had a tendency to have speech disorders. Articulation disorders in the phoneme /s/z/d/l/t/ become the dominant problem experienced by patients with AOB. Anterior open bite (AOB) is a form of malocclusion that causes more articulation disorders than other malocclusions. The presence and position of the tongue are thought to have a substantial influence on articulation disorders.